Pengaruh Penambahan Limbah Plastik PET (Polythylene Terepthalate) Untuk Aspal Penetrasi 60/70 terhadap Karakteristik campuran Aspal (AC-BC) - Alfia Nur Rahmawati; Budi Hadi Prasetyo (Wahana Teknik, 2022)
Asphalt is one of the materials used as road pavement material, this material was chosen because of its good and comfortable final result as flexible pavement. One way to prevent damage to the pavement due to vehicle loads is to improve the quality and stability of the pavement. Therefore, the use of additives is an alternative. Plastic basic materials that are difficult to decompose need to be handled properly in addition to recycling solutions with an increase in their functional value. Utilization of plastic waste as an additional material in the AC-BC (Asphalt Concrete-Binder Course) layer mixture in order to increase its stability value, as well as one of the concrete steps to reduce waste that is difficult to decompose by increasing its function value. In this function value. In this study, the addition of PET (Polyethylene Terephthalate) plastic to the AC-BC asphalt mixture affected the value of the marshall characteristics. With the effect caused by the addition of PET plastic, the higher the percentage of the mixture, the higher the percentage of the mixture, the higher the stability, VMA, VIM, and MQ values formed. Meanwhile, the value of VFB and flow tends to decrease as the PET plastic content increases. The percentage of addition of PET plastic to the AC-BC asphalt mixture also affects the density value where the higher the percentage value, the lower the density value and can increase the VIM value. So that the asphalt mixture will visually have a lot of voids.